The lung, the niche, and the microbe: Exploring the lung microbiome in cancer and immunity - Huynh, Mai; Crane, Meredith J.; Jamieson, Amanda M. (Frontiers in Immunology, 2023)
Lung cancer is the third most common cancer worldwide with the highest mortality rate amongst cancers due to the difficulty of an early diagnosis. Even more, lung cancer has remained obstinate to most cancer therapeutics, with immunotherapy showing mild promise. In order to combat the toxicity resulting in the rigorous immune response induced by immunotherapy, it becomes pertinent to resolve the minutiae of the lung tumor microenvironment while more specifically probing the pulmonary immunity that recognize and respond to tumors. Many recent studies have demonstrated that the lung microbiome is dynamic during both health and disease, and these changes have a dramatic effect on modulating regulatory immune responses during diseases such as cancer. However, because the microbial biomass of the lung is limited, microbiome studies on lung cancer have primarily focused on the gut microbiome. In this review, we give relevant background to the lung microbiome, the respiratory system, and pulmonary immunity, and put these topics in the context of the immune response to lung cancer. While we describe the current research on the lung microbiome and lung cancer, we also draw attention to the numerous and relevant unanswered questions and point to potential areas of research.